Functional Movement Screen Detected Asymmetry & Normative Values Among College-Aged Students - Craig R Triplett; Bryan S Dorrel; Matthew L Symonds; Corey A Selland; Daniel D Jensen; Christopher N Poole (International Journal of Sports Physical Therapy)
# Background